Optimal roughening of convex bodies - Plakhov, Alexander (2012)
A body moves in a rarefied medium composed of point particles at rest. The particles make elastic reflections when colliding with the body surface, and do not interact with each other. We consider a generalization of Newton’s minimal resistance problem: given two bounded convex bodies C1 and C2 such that C1 ⊂ C2 ⊂ R3 and ∂C1 ∩ ∂C2 = ∅, minimize the resistance in the class of connected bodies B such that C1 ⊂ B ⊂ C2. We prove that the infimum of resistance is zero; that is, there exist ”almost perfectly streamlined” bodies.